Typology of Myth Between the Legend of Lake Toba and the Creator of Lake Chala - Raihan Syach Bustami Harahap; Ice Sariyati; Agry Pramita (Hasanuddin University, 2025)
Mythology or myth is an important part of the study of literature. A comparative study of two literary works written in the same language and originating from the same cultural context is not a valid application of this field. This study employs a comparative literature methodology to examine the similarities, differences, and classifications of myths associated with the Legend of Lake Toba and the Creator of Lake Chala. This research utilized a comparative literature framework to analyse the myths associated with the research subjects. This study employed a qualitative research design utilizing descriptive analysis and library research. Both narratives employed the established plot structure identified as Freytag’s pyramid. Despite the narrative differences, the plots of the two stories are theoretically analogous. The Legends of Lake Toba and Lake Chala exhibit significant similarities, particularly in their narrative structures, cautionary motifs, and consequences of unmet obligations. Based on the noted similarities and differences, particularly in the plot, the authors concluded that both The Legend of Lake Toba and The Creator of Lake Chala fit within the speculative and explanatory (etiological) category of myths.